THE EFFECT OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE ON CONTINUANCE INTENTION WITH TRUST AS AN INTERVENING VARIABLE FOR GOPAY USERS IN TUAH MADANI DISTRICT - Zuleman, Aldi; Rachmad, Ferizal (International Journal of Business and Information Technology, 2026)
The rising trend in e-wallet usage, particularly among the youth demographic, has significantly contributed to the convenience and efficiency of digital-based financial transactions. The purpose of this study is to determine the influence of perceived usefulness and perceived ease of use on Continuance Intention, with trust serving as an intervening variable among GoPay users in Tuah Madani District. The research method employed is quantitative with a survey approach. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) through the SmartPLS application. This study involved a population of unknown size, with the sample size determined using the Cochran formula, resulting in 96 respondents. The results of the study indicate that perceived usefulness and perceived ease of use have a positive and significant effect on trust; furthermore, perceived usefulness, perceived ease of use, and trust have a positive and significant effect on Continuance Intention. Additionally, trust significantly intervenes in the influence of perceived usefulness and Perceived ease of use on Continuance Intention. Based on the coefficient of determination, it is known that the Continuance Intention construct can be explained by the variables perceived usefulness (X1), Perceived ease of use (X2), and trust (Z) by 87.4%, while the remaining 12.6% is influenced by other variables outside the study. Furthermore, the trust (Z) construct can be explained by the variables perceived usefulness (X1) and Perceived ease of use (X2) by 74.2%, while the remaining 25.8% is influenced by other variables outside the study.